Spatial Cleaning Action of Ultrasonic Irrigation on Enterococcus faecalis Biofilm - Michael C.C. Tse; Gary S.P. Cheung (MDPI AG, 2020)
This study aimed to examine the spatial cleaning effect of ultrasonic irrigation in simulated root canal with oblong cross section in the absence of antimicrobial agent. A 7-day E. faecalis biofilm was cultivated in a rectangular, simulated canal model and subjected to passive ultrasonic irrigation (PUI) with sterile saline for 5 minutes. After that, the biofilm was examined by confocal microscopy after bacterial viability staining at 58 sites around and beyond the endosonic file. Results showed that, at the vicinity of the file, the amount of viable bacteria ranged from 13.1% (2.75 mm from the tip) to 40.5% (4.5 mm level). Lesser amounts of live bacteria were observed within 1 mm from the vibrating file, which amount increased for sites farther away. At 3 mm distance, the amount of bacteria (35.5 to 64.4%) was significantly greater than areas situated close to the vibrating file (P < 0.01). Sites next to the anti-nodes of file had less bacteria remaining than sites near the nodes (P = 0.050). Apically (0.5 mm or more), the amount of bacteria was significantly greater than that at the file tip (16.4%) (P < 0.05). It was concluded that PUI is able to dislodge a single-species biofilm, provided that they are situated in close vicinity to the vibrating file.